Search for antibiotic-resistant strains of Gram-positive and Gram-negative microorganisms in poultry products - Alisseiko, Y.G.; Belyaev, I.A.; Turemuratova, A.B. (Fundamental and Experimental Biology, 2024)
Research on the search for antibiotic-resistant strains of Gram-positive and Gram-negative microorganisms in poultry products is an urgent and important topic in modern medicine and the food industry. Antibiotics are widely used in poultry farming for the prevention and treatment of infections, but this also contributes to the development of antibiotic resistance in microorganisms. The purpose of this study is to identify and assess the level of antibiotic resistance of Gram-positive and Gram-negative bacteria present in meat and poultryderived products. The methods include analyzing food samples, namely chicken fillets and chicken eggs, for the presence and identification of resistant strains, as well as testing their sensitivity to various antibiotics. During the study, it was found that 19.05 % of Gram-positive strains and 26.09 % of Gram-negative strains isolated from farm products exhibit resistance or multi-resistance properties. At the same time, 58.28 % of Gram-positive and 59.42 % of Gram-negative microorganisms also exhibit resistance or multi-resistance properties.